2016
DOI: 10.1017/s0021932016000651
|View full text |Cite
|
Sign up to set email alerts
|

SOCIOECONOMIC INEQUALITIES IN SELF-REPORTED HEALTH AND PHYSICAL FUNCTIONING IN ARGENTINA: FINDINGS FROM THE NATIONAL SURVEY ON QUALITY OF LIFE OF OLDER ADULTS 2012 (ENCaViAM)

Abstract: This study aimed to evaluate educational and income inequalities in self-reported health (SRH), and physical functioning (limitations in Activities of Daily Living (ADL)/Instrumental Activities of Daily Living (IADL)), among 60-year-old and older adults in Argentina. Using cross-sectional data from the Argentinian National Survey on Quality of Life of Older Adults 2012 (Encuesta Nacional sobre Calidad de Vida de Adultos Mayores, ENCaViAM), gender-specific socioeconomic inequalities in SRH and ADL and IADL limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Well-educated adults may possibly access sufficient and high-quality information [19,20,31], which helps them have a better understanding of what to options choose to guarantee healthy conditions. Thus, disadvantages in economic status and in education attainment contribute a lot to the inequalities in long-term care needs, which were consistent with the results of previous studies in developed countries [32][33][34][35]. The results of this study are discouraging for the following reasons when extending universal coverage of long-term care insurance.…”
Section: Discussionsupporting
confidence: 90%
“…Well-educated adults may possibly access sufficient and high-quality information [19,20,31], which helps them have a better understanding of what to options choose to guarantee healthy conditions. Thus, disadvantages in economic status and in education attainment contribute a lot to the inequalities in long-term care needs, which were consistent with the results of previous studies in developed countries [32][33][34][35]. The results of this study are discouraging for the following reasons when extending universal coverage of long-term care insurance.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have investigated the association between multimorbidity and health outcomes, both physical [6][7][8][20][21][22], and mental [6,8,23,24], but many were either small [7,21], not representative for the entire country [8,23], focused on a specific subgroup like elderly [6,7,21,22], or focused on a limited number of chronic diseases [24][25][26]. There are many papers on socio-economic inequalities in health, which clearly demonstrate that lower SES is associated with greater mortality [27,28], higher prevalence of multimorbidity [29] and worse health outcomes [30] To the best of our knowledge, none of them investigated how the association between multimorbidity and health varies by SES.…”
Section: Introductionmentioning
confidence: 99%
“…For the cognitive function, a study conducted in England, in which socioeconomic inequality was considered in childhood (father's occupation) and in adulthood (occupation of the head of the household), found that older adults with a better SES had a better cognitive performance compared to those with a worse SES. 27 Specifically, it was reported that a lower SES in childhood resulted in a lower verbal memory, measured through the evocation of correct words (SII=-4.72; 95%CI:-5.84,-3.61), and a similar association was found (SII=-6.67; 95%CI:-5.84,-3.61) for the same indicator in adulthood. In our study, which used the verbal fluency test (which consists in correctly evoking as many animals as possible), we found a similar association in direction and magnitude (SII=-1.76; 95%CI:-2.72,-0.79).…”
Section: Discussionmentioning
confidence: 89%